2020
DOI: 10.1021/acs.jmedchem.0c00618
|View full text |Cite
|
Sign up to set email alerts
|

Design and Structural Optimization of Dual FXR/PPARδ Activators

Abstract: Nonalcoholic steatohepatitis (NASH) is considered as severe hepatic manifestation of the metabolic syndrome and has alarming global prevalence. The ligand-activated transcription factors farnesoid X receptor (FXR) and peroxisome proliferator-activated receptor (PPAR) δ have been validated as molecular targets to counter NASH. To achieve robust therapeutic efficacy in this multifactorial pathology, combined peripheral PPARδ-mediated activity and hepatic effects of FXR activation appear as a promising multitarge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 23 publications
0
22
0
Order By: Relevance
“…Following this strategy, we have previously developed dual modulators to target, for example, farnesoid X receptor (FXR) and soluble epoxide hydrolase (sEH),[ 6 , 7 , 8 ] or FXR and peroxisome proliferator‐activated receptors (PPARs). [ 9 , 10 ] Strong therapeutic efficacy of such multi‐target agents in preclinical NASH models[ 10 , 11 ] corroborates the potential of designed polypharmacology in this indication. We further hypothesize that a combination of partial FXR activation [12] and inhibition of leukotriene A4 hydrolase (LTA4H) can efficiently counteract NAFLD/NASH.…”
Section: Introductionmentioning
confidence: 85%
See 2 more Smart Citations
“…Following this strategy, we have previously developed dual modulators to target, for example, farnesoid X receptor (FXR) and soluble epoxide hydrolase (sEH),[ 6 , 7 , 8 ] or FXR and peroxisome proliferator‐activated receptors (PPARs). [ 9 , 10 ] Strong therapeutic efficacy of such multi‐target agents in preclinical NASH models[ 10 , 11 ] corroborates the potential of designed polypharmacology in this indication. We further hypothesize that a combination of partial FXR activation [12] and inhibition of leukotriene A4 hydrolase (LTA4H) can efficiently counteract NAFLD/NASH.…”
Section: Introductionmentioning
confidence: 85%
“…One such disease is NASH which arises from metabolic imbalance, inflammation and fibrotic transformation in liver, and hence demands therapeutic intervention against several factors. Previous studies have shown that designed multiple ligands of FXR and sEH,[ 6 , 7 , 8 ] PPARα and PPARδ [35] as well as FXR and PPARδ[ 9 , 10 ] hold potential to achieve superior efficacy in experimental NASH treatment. Here we report a novel designed multiple ligand that concomitantly activates FXR and inhibits LTA4H.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…23,24 These include combining FXR agonism with PPAR agonism. 64,65 FXR agonism has been combined with PPAR and combined PPAR/ agonism. 64,65 These combined FXR and PPAR agonists have demonstrated promise in liver diseases but have yet to be tested in kidney diseases.…”
Section: Other Potential Multi-target Drugs For Kidney Diseasesmentioning
confidence: 99%
“…64,65 These combined FXR and PPAR agonists have demonstrated promise in liver diseases but have yet to be tested in kidney diseases. 64,65 PPAR agonism has also been coupled to glucokinase activation and AT1 receptor inhibition. 23,24 Renin angiotensin system angiotensin converting enzyme (ACE) inhibition has been combined with dipeptidyl-peptidase 4 (DPP4) inhibition.…”
Section: Other Potential Multi-target Drugs For Kidney Diseasesmentioning
confidence: 99%